A system dynamics model to analyse the impact of environment and economy on scenic's sustainable development via a discrete graph approach. Issue 1 (1st February 2017) - Liao, Zhixue; Ren, Peiyu; Jin, Maozhu; Zhang, Zhenzhong
Abstract : Sustainable development is the key factor which attracts managers and scenic scholars attention. In the scenic system, economic subsystem, environment subsystem and scenic space subsystem are the major factors affecting the scenic sustainable development. In this paper, we analyze the relationship among them and build a system dynamics model to simulate the operation of scenic system which can show scenic states in the future. In order to provide workable proposals for sustainable development, we take Jiuzhai Valley as a research object, and use sensitivity analysis to find the impact of quantity of pollutants discharged, quantity of pollutants disposed, and average daily tourist reception capacity on the scenic development. From the sensitivity analysis, we conclude that adjusting quantity of pollutants discharged and disposed and average daily tourist reception capacity can improve the sustainable development of scenic. Finally, Some suggestions are put forward to Jiuzhai Valley managers.